Bioorthogonal Chemistry Enables Single‐Molecule FRET Measurements of Catalytically Active Protein Disulfide Isomerase. (29th September 2020) - Chinnaraj, Mathivanan; Barrios, David A.; Frieden, Carl; Heyduk, Tomasz; Flaumenhaft, Robert; Pozzi, Nicola
Abstract: Folding of newly synthesized proteins in the endoplasmic reticulum is assisted by several families of enzymes. One such family is the protein disulfide isomerases (PDIs). PDIs are oxidoreductases, capable of forming new disulfide bonds or breaking existing ones. Structural information on PDIs unbound and bound to substrates is highly desirable for developing targeted therapeutics, yet it has been difficult to obtain by using traditional approaches because of their relatively large size and remarkable flexibility. Single‐molecule FRET (smFRET) could be a powerful tool to study PDIs' structure and dynamics under conditions relevant to physiology, but its implementation has been hindered by technical challenges of position‐specific fluorophore labeling. We have overcome this limitation by site‐specifically engineering fluorescent dyes into human PDI, the founding member of the family. Proof‐of‐concept smFRET measurements of catalytically active PDI demonstrate, for the first time, the feasibility of this approach, expanding the toolkit for structural studies of PDIs. Abstract : The click that does the trick : PDI is the founding member of a large family of cysteine‐dependent enzymes essential for protein folding and an attractive target of drug development. This study reports the position‐specific labeling of PDI through biorthogonal chemistry, and the first application of smFRET to investigate PDI's conformational dynamics in solution.